6g+3(-8+4g)=1-g

Simple and best practice solution for 6g+3(-8+4g)=1-g equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6g+3(-8+4g)=1-g equation:


Simplifying
6g + 3(-8 + 4g) = 1 + -1g
6g + (-8 * 3 + 4g * 3) = 1 + -1g
6g + (-24 + 12g) = 1 + -1g

Reorder the terms:
-24 + 6g + 12g = 1 + -1g

Combine like terms: 6g + 12g = 18g
-24 + 18g = 1 + -1g

Solving
-24 + 18g = 1 + -1g

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add 'g' to each side of the equation.
-24 + 18g + g = 1 + -1g + g

Combine like terms: 18g + g = 19g
-24 + 19g = 1 + -1g + g

Combine like terms: -1g + g = 0
-24 + 19g = 1 + 0
-24 + 19g = 1

Add '24' to each side of the equation.
-24 + 24 + 19g = 1 + 24

Combine like terms: -24 + 24 = 0
0 + 19g = 1 + 24
19g = 1 + 24

Combine like terms: 1 + 24 = 25
19g = 25

Divide each side by '19'.
g = 1.315789474

Simplifying
g = 1.315789474

See similar equations:

| 46+2x-x=27 | | -4(v+4)=3(v+4)+7 | | 2x^2+35x-123=0 | | x-(-7)=-21 | | x=3x-12 | | 5(4x+3)=35 | | 3.4t+0.08=4 | | m+10=-2 | | 2y+8=33 | | 2+2x=x+4 | | 13x-7=2+910x | | 2(m+2)+4=m | | 2(0)+4=x | | 4(2x-3)+5=-71 | | 2(-3)+4=x | | 16s+10=4 | | -2(x+9)=-36 | | 4a+7(a-4)+6(a+8)=9 | | 2y+66=3y-24 | | 7y=44 | | x+4=2y | | 3(2)= | | 2-6-5-13-(-25)=p | | (2)(2)(2)= | | 8x-6x=-2 | | 28-(-8)-3=m | | x^2+x+0.5=0 | | 11d=11 | | X=-8+5x | | -12-25-32-(-9)=p | | -4-4=8-7x | | 15y=150 |

Equations solver categories